Study on spontaneous combustion characteristics of water-soaked air-dried coal samples in high ground temperature condition - Xin LI (Meikuang Anquan)
Under the influence of high ground temperature and high water gushing in deep mining in Longdong Mining Area, the physical and chemical characteristics of coal left in goaf are changed, which affects its spontaneous combustion characteristics. In order to study the oxidative spontaneous combustion characteristics and influencing mechanism of residual coal under the action of water soaking and air drying at high temperature, the types and contents of active groups, the intensity of heat release at each oxidation stage, the microscopic pore structure of coal and the characteristics and changes of oxygen diffusion coefficient were investigated by infrared spectrum analysis, microthermal experiment, low-field nuclear magnetic resonance experiment and molecular dynamics simulation experiment. The results show that the content of −CH3/−CH2−, −CH3−, −CH2−, −C=O−, −COOH, substituted benzene and −C=C− in the water-soaked air-dried coal samples at high temperature is higher than that of the original coal samples. The oxygen-containing functional group side chain and aliphatic hydrocarbon are the key active groups in the molecular structure of coal, and their content is positively correlated with the self-heating capacity of coal oxidation. During the transition from the slow oxidation stage to the early stage of intense oxidation, the peak heat release intensity of the water-soaked air-dried coal sample under high temperature conditions is 509 mW, and that of the original coal sample is 398 mW, the former is 27.9% higher than the latter. At the inflection point of coal sample heat release rate, the heat release intensity of the former is 338 mW and 268 mW respectively, and the former is 26.1% higher than the latter. After high temperature water soaking and air drying, the heat release intensity and growth rate of coal body oxidation are significantly improved. The oxygen diffusion coefficient on the coal surface increases synchronously with the increase of the pore size, and the oxygen diffusion coefficient increases from 1.89×10−8 m2/s at 1 nm to 17.13×10−8 m2/s at 6 nm. The development of microscopic pores improves the oxygen diffusion and transport capacity in the environment.